1997
DOI: 10.2337/diab.46.2.187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fatty Acids in Mediating the Effects of Peripheral Insulin on Hepatic Glucose Production in the Conscious Dog

Abstract: We investigated the mechanism by which a selective increase in arterial insulin can suppress hepatic glucose production in vivo. Isotopic (3-3H-glucose) and arteriovenous difference methods were used in overnight-fasted, conscious dogs. A pancreatic clamp (somatostatin, basal portal insulin, and glucagon infusions) was used to control the endocrine pancreas. Equilibration (100 min) and basal (40 min) periods were followed by a 180-min test period. In control dogs (n = 5), basal insulin delivery was continued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 0 publications
4
92
1
Order By: Relevance
“…A large body of evidence concerning hepatic glucose metabolism during exercise in diabetes has been derived from animal experiments [18][19][20][21][22] but there is a lack of in vivo human data. Human studies using magnetic resonance spectroscopy (MRS) have reported defects in mobilisation of hepatic glycogen stores in patients with type 1 diabetes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence concerning hepatic glucose metabolism during exercise in diabetes has been derived from animal experiments [18][19][20][21][22] but there is a lack of in vivo human data. Human studies using magnetic resonance spectroscopy (MRS) have reported defects in mobilisation of hepatic glycogen stores in patients with type 1 diabetes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…increased adipocyte mass and impaired insulin regulation of lipolysis [11] could increase NEFA, flux to other tissues like skeletal muscle thus increasing their triglyceride storage [12,13], altering the hepatic glucose output [14] and insulin secretion. Increased fat accumulation can also act in a paracrine and/or endocrine way to promote insulin resistance by thus far unknown mechanisms [15].…”
mentioning
confidence: 99%
“…Although insulin inhibits key enzymes of gluconeogenesis (1) and the mobilization of gluconeogenic substrates to the liver (2)(3)(4)(5), it is well established that insulin-induced hypoglycemia (IIH) provokes the release of hormones (6)(7)(8)(9)(10)(11), which stimulate hepatic gluconeogenesis (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%